Toward Sustainable Halal Tourism: Muslim-Friendly Smart Tourism Experiences and Environmental Sustainability as Determinants of Tourist Satisfaction - Nazwa Halimatusya’diah; Bethani Suryawardani; Sampurno Wibowo (Lembaga Riset Ilmiah, 2026)
The increasing populationThe increasing number of global Muslim tourists, projected to reach 300 million trips per year by 2030, drives the need for a technology-based and sustainable halal tourism model. This study examines the influence of Muslim-Friendly Smart Tourism Experience (MFST) and Environmental Sustainability (ES) on Muslim Traveler Satisfaction (TS), with Muslim Perception (MP) as a mediator. Unlike previous studies, this research is the first to test MP as a dual mediator that simultaneously bridges the technological and ecological pathways within a single structural model, conducted at a natural-geological destination designated as a conservation area (Kawah Putih Ciwidey). A quantitative approach was applied to 210 Muslim respondents using a 5-point Likert scale questionnaire, analyzed via PLS-SEM using SmartPLS. All seven hypotheses were supported: MFST and ES have a positive effect on MP and TS; MP is the strongest predictor of satisfaction (t = 8.315, p = 0.000, f² = 0.427) while significantly mediating both pathways. The model explains 45.4% of the variance in MP and 49.9% of the variance in TS. The findings demonstrate that Muslim perceptions function as an interpretive filter that transforms destination attributes into meaningful satisfaction—a mechanism that has not been empirically tested in previous literature. Destination managers are advised to prioritize halal digital ecosystems and environmental conservation programs communicated through an Islamic values framework. of Muslim visitors globally offers major prospects for the advancement of technology-driven and sustainable halal tourism. This study seeks to examine the impact of Muslim-friendly smart tourism experiences and environmental sustainability on Muslim visitor satisfaction, while also investigating the mediating effect of Muslim attitudes. A quantitative approach was utilised including a sample of 210 Muslim participants who had visited Kawah Putih Ciwidey, employing a 5-point Likert scale questionnaire. The investigation employed structural equation modelling (SEM) to evaluate the mediation hypothesis. The findings demonstrate that Muslim-friendly smart tourism experiences substantially impact tourist happiness, as does environmental sustainability. Muslim attitudes were identified as significant mediators in both correlations. Theoretical implications present a cohesive model that situates Muslim perceptions as a psychological conduit, whereas practical implications furnish recommendations for the formulation of sustainable halal tourism policies in Indonesia.